Pengembangan model sekolah berkarakter budaya di sekolah dasar di kecamatan Ngaglik - Dwijonagoro, Suwarna; Endraswara, Suwardi; Nurhidayati, Nurhidayati (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2020)
This research aims to develop school implementation guidance based on culture by government regulation no. 5 / 2011. Research and development (R & D) design use Allesi-Trollip model. Allesi-Trollip model consists of planning, designing, validating, revising, up to become a final product. Results of this research and development are (1) this research was successfully developed two books : (I) Rencana Tindakan Pengembangan Sekolah Berbasis Budaya and (II) Contoh Implementasi Pengembangan Sekolah Berbasis Budaya nilai Sopan Santun. These books which have been assessed by experts and got the score 4,36 (satisfactory). Assessment by the head of the primary school got score 4.39 (satisfactory). The average of these scores is 3.38 which also means satisfactory, and (3) The main qualitative results is SBB will soon to be socialized and implemented at elementary school which accompanied by Yogyakarta State University experts and supported by Dikpora.